Management of Energy-Efficiency in the Context of New Climate Policy - Pakhomova, Nadezda Victorovna; Richter, Kurt Knut; Zhigalov, Viacheslav Mikhaylovich; Malova, Aleksandra Sergeevna (Economy of Regions, 2017)
We paper examines the improvement of the energy-efficiency in Russian regions as one of the leading directions of Russia's response to the new global challenges and the implementation of Paris climate agreement (2015) on reducing of greenhouse gases emissions. Пє research aims at the justification of differentiated strategies and instruments to control energy-efficiency in Russian regions with respect to its key drivers. We focuse on a regional aspect as there are essential reserves and distinctions of regions by energy efficiency level, the need of problem areas' identification, generalization and systematization of positive experience. Based on actual data, we verify the hypothesis that the energy-intensity level of the gross regional product depends on the share of energy-intensive industries, on the region's land area and on climate characteristics. Institutional factors having positive or negative influence have to be regarded as well. We have untilized comparative method, correlation and cluster analyse, conceptions of new public government and control by results, applied to problems of energy-efficiency and climate risks. As a result, we have identified three groups of regions. In one of them, was no statistically significant dependence of the energy intensity from the applicable standard factors proved. We two other groups confirm this dependence, but with significant differences in the level of energy efficiency. Furthermore, the study shows the significance of regional sector structure factor and justifies differentiated strategies to reduce energy consumption by regional and federal regulators and their consideration in the Energy strategy 2035. We measures to improve the energy efficiency in the regions are to be integrated into the long-term strategy of the Russian Federation to reduce greenhouse gases emissions (2050); and the innovation activities and the quality of regional energy-efficiency management are to be considered and analised.